2007
DOI: 10.1073/pnas.0610216104
|View full text |Cite
|
Sign up to set email alerts
|

In the regulation of cytochrome P450 genes, phenobarbital targets LKB1 for necessary activation of AMP-activated protein kinase

Abstract: Transcriptional activation of cytochrome P450 (CYP) genes and various drug metabolizing enzymes by the prototypical inducer phenobarbital (PB) and many other drugs and chemicals is an adaptive response of the organism to exposure to xenobiotics. The response to PB is mediated by the nuclear receptor constitutive androstane receptor (CAR), whereas the chicken xenobiotic receptor (CXR) has been characterized as the PB mediator in chicken hepatocytes. Our previous results suggested an involvement of AMP-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 41 publications
2
56
0
Order By: Relevance
“…A recent report speculated that one of the AMPK activation mechanisms might be the ROS (27), because it was demonstrated that various therapeutic effects of naturally occurring compounds involved a release of ROS. We next tested whether AMPK activation was involved in the stimulatory process of ROS production by treating theaflavins.…”
Section: Theaflavins Induce Ampk Phosphorylation Through the Lkb1 Patmentioning
confidence: 99%
“…A recent report speculated that one of the AMPK activation mechanisms might be the ROS (27), because it was demonstrated that various therapeutic effects of naturally occurring compounds involved a release of ROS. We next tested whether AMPK activation was involved in the stimulatory process of ROS production by treating theaflavins.…”
Section: Theaflavins Induce Ampk Phosphorylation Through the Lkb1 Patmentioning
confidence: 99%
“…However, the results from the mechanistic study of the AMPK-dependent activation of CAR leave much to be desired. Phenobarbital seems to increase the AMP/ATP ratio and promote liver kinase B1 (LKB1)-mediated AMPK activation [31] . Another pathway involving the microRNA miR-122 is also associated with AMPK activation [32] .…”
Section: Nuclear Translocation Of Carmentioning
confidence: 99%
“…We next explored the role of AMPK in NaHS regulation of high glucose-stimulated protein synthesis. We employed Compound C, a selective inhibitor of AMPK (35)(36)(37). Preincubation with Compound C abrogated the ability of NaHS to increase AMPK phosphorylation in high glucose-treated cells at 30 and 60 min (p Ͻ 0.05, p Ͻ 0.01 versus GluϩNaHS) (Fig.…”
Section: Hydrogen Sulfide Decreases High Glucose-induced Proteinmentioning
confidence: 99%